Explaining Inequality Between Countries: The Declining Role of Political Institutions - Andrew J. Hussey; Michael Jetter; Dianne McWilliam (Center for Economic Studies and ifo Institute (CESifo), 2017)
Within the fundamental determinants of cross-country income inequality, `humanly devised' political institutions represent a hallmark factor that societies can influence, as opposed to, for example, geography. Focusing on the portion of inequality explainable by differences in political institutions, we decompose annual cross-country Gini coefficients for 95 countries (representing 85 percent of the world population) from 1960-2012. Since 1988, inequality has marginally decreased (from a Gini of 0.525 to 0.521) but the portion that cannot be explained by political institutions has increased substantially (from 0.411 to 0.459). Specifically, the explanatory power of institutions fell rapidly from the late 1980s to the early 1990s. This result prevails when using alternative variables, expanding the sample, weighting countries by population size, and controlling for the remaining fundamental determinants of income: culture and education. Over the same timeframe, the explanatory power of geographical conditions has been rising. This phenomenon appears to be global and is unlikely to be driven by contemporary regional events alone, such as the fall of the Soviet Union, Asian success stories (e.g., China), or institutional monocropping in Africa. A corollary of our finding implies that, if we hold societies responsible for their political institutions, inequality has become notably less fair since the late 1980s.
Keywords: D63; D72; E02; O11; O43; O47; 330; fairness of income inequality; fundamental determinants of development; international inequality; political institutions